Auditoria de gestión al departamento de talento humano y su incidencia en el proceso administrativo del gobierno autónomo descentralizado municipal del cantón Quevedo, provincia de Los Ríos, periodo 2011-2012 - Suarez Villarreal, Kenny Leandro (2013)
The present investigation topic develops an analysis of the administrative Administration in an institution of services belonging to the State, like he/she is the Decentralized Autonomous Government of the Canton Quevedo; the evaluation is directed to the area of the department of human talent that looks for to use a modern methodology of control of administration called square of integral control; under this context the indicators are designed that evaluate the efficiency, effectiveness and economy in the benefit of the service, helping to the institution of services to improve the use of their human resources and materials. In the Ecuador they exist some laws and norms of the public sector that frame the existence of a control system in the government's dependent entities for this reason, this work it is based in a system of indicators and the design of processes that optimize the resources and improve the productivity, on the normative bases of the necessary internal control for the execution of the proposed objectives according to the laws. With the development of this work an integral vision of the organization is obtained, with respect to if it is reaching the objectives and goals that he/she has thought about, likewise the used resources and the executed actions, with the purpose of evaluating its administration to redefine its strategies in the case that you amerite. This system also collaborates for the realization of administration audits in the public sector. The present investigation project is compound for two segments, the first one corresponds to the introductory part and the second to the chapters that constitute the body of the document in a number of five. This investigation consists of a documental or theoretical part and another practice. It is considered documental for that their objective was reached with the application of theories or advance of general order already existent and whose effects are known in the professional environment of the accounting. It is considered practice because the necessary information, to achieve the outlined objective, was obtained directly of the reality. To develop the theoretical mark of the investigation it became precise to analyze each one of the variables that are presented as a result of the position of the problem, it was necessary the search of opportune and truthful information in books, scientific articles, pamphlets and pages web that fulfilled the technical requirements characteristic of a scientific writing to my concept. As for the methodology of the investigation, methods like the inductive, deductive and analytic were used, since I consider that they are the most opportune when of executing an audit it is. As for the techniques, it became necessary to appeal to the interview, since it is the most direct method to obtain information on the part of the speaker. The execution of this work, included the evaluation of the internal control by means of 20 questions, having 70 points as a result on a total of 98 points; inside the discoveries they were had: the lack of periodic reports, nonexistence of a mechanism that measures the execution of objectives and the lack of yield indicators. As for the level of trust we obtained 71,43%, therefore we have 28,57% of level of control risk; the mensuration of the risks has: risk inherent 34%; risk of control 28,57%; and the detection risk assumed a 0,15; giving a 1,46 of the audit risk as a result. As part essential of this investigation project, they think about conclusions and recommendations in the chapter V, these recommendations to my approach will contribute from an appropriate way to the administration of the department of human talent of the Municipal Decentralized Autonomous Government of the Canton Quevedo.